Heidegger, Physics and the Question of Technique - Giannetto, Enrico R.A. Calogero (Mechane, 2022)
Heidegger’s position on technique has been analyzed in very many papers. Heidegger departed from Husserl’s position that gives only instrumental value to technique and to science. Heidegger, as well known, discussed a non-instrumental, non-technical role of technique, but rather revealing of being. Heidegger’s discourse has always remained strange and abstract to the eyes of his interpreters: it becomes understandable if it is read as a phenomenological, philosophical, elaboration of Bachelard’s phénoménotechnique.